Caracterisation Sedimentologique Et Hydrodynamique Des Formations Sableuses Du Miocene Inferieur De La Region D’eboinda (Sud-Est De La Cote d’Ivoire) - Toé Bi, Kizito Katel Kahou; Yao, N’goran Jean-Paul; Kessé, Touvalé Marcel; Digbéhi, Zéli Bruno (European Scientific Journal, ESJ, 2016)
Five hundred and five (505) cuttings samples of 51 survey (of 10 m depth maximum) drilled in Eboinda area (South-western of Côte d’Ivoire) were subject to lithological, mineralogical an granulometry studies in order to clarify the nature of sediments and factors and processes involved during their transport and deposition. The "Surfer" software helps to map the formations. The results indicate: - lithologically:, six mains facies were defined ; sandy clays with gravel, clayey sand, sands, siltyey clay, sandy clays and clay. Sandy sediments were mapped to north and clayed one in south of the study area. Most of studied sands were interpreted as river and coastal dune deposits. Many minerals were described such as sphene, zircon, tourmaline, ilmenite, hematite, apatite, limonite, sillimanite, chromite, muscovite, garnet, chlorite, rutile, goethite, quartz and feldspar. The clay fraction is composed by kaolinite, quartz, apatite, gypsum, goethite and halloysite; - hydrodynamically: the surfacecreep is the main mode of transport expressed within units III and VI. While saltation characterizes sand units IV and V. Predominance of rounded forms and sub-rounded features of quartz grains suggests a transport in aqueous zone over a long distance. In the other hand the sands of units VI and III are essentially sub-angular, suggesting a close generating source. The blunt and shiny aspect of most sands grains encountered, confirm the mode of transport in aqueous zone.